Characterization of Biochemical Risk Factors of Senile Cataract Among Adults Visiting Komfo Anokye Teching Hospital, Kumasi, Ghana. - Antwi, Amos Osei (2016)
A thesis submitted to the Department of Molecular Medicine, School of Medical Sciences. Kwame Nkrumah University of Science and Technology in partial fulfillment for the degree of Master of Science.